OPTIMIZATION OF SPEED QUALITIES IN SPRINTERS IN THE SENSITIVE PERIOD OF 14-17 YEARS - Sorokin D.V. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to substantiate a training methodology that takes into account age-related characteristics for maximum potential of athletes. Methods and structure of the study. The methodology includes an analysis of modern approaches, such as the development of explosive strength (squats, lunges), improvement of running technique (correction of posture, step rhythm) and reaction training (variable starting signals). Physiological aspects are considered, including hormonal changes (testosterone in boys, estrogen in girls), development of the nervous system and genetic predisposition to fast muscle fibers, as well as psychological factors – motivation and stress resistance. Results and conclusions. The analysis showed that the sensitive period opens up wide opportunities for the development of speed qualities due to the high adaptability of the neuromuscular system. A combination of strength exercises, technical work and starting training significantly improves the indicators. It is necessary to balance loads and recovery, individualize programs and integrate psychological preparation for stress management. The implementation of adapted plans should be combined with alternating phases and monitoring of the physical condition. Thus, an integrated approach that combines physical development, technical improvement and psychological support is essential for the successful preparation of sprinters and can be used in youth sports to optimize training and minimize the risk of overload.